Discretionary Justice : Looking Inside a Juvenile Drug Court - Paik, Leslie (Book collections on Project MUSE., 2011)
Juvenile drug courts are on the rise in the United States, as a result of a favorable political climate and justice officials' endorsement of the therapeutic jurisprudence movement--the concept of combining therapeutic care with correctional discipline. Discretionary Justice overviews the system, taking readers behind the scenes of the juvenile drug court. Based on fifteen months of ethnographic fieldwork and interviews at a California court, Leslie Paik explores the staff's decision-making practices in assessing the youths' cases, concentrating on the way accountability and noncompliance are.